2013
DOI: 10.1093/sw/swt050
|View full text |Cite
|
Sign up to set email alerts
|

Group Work with Bereaved Individuals: The Power of Mutual Aid

Abstract: Group work has been underused as an intervention with grieving clients. This is despite the fact that group membership offers bereaved individuals a number of unique advantages. In this article, the use of group work with bereaved individuals is examined, based on current theory and research. The role and skills of the group worker are identified and illustrated through the use of case examples. Challenges associated with working with groups for bereaved individuals also are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Members in the groups bene t from opportunities to give, not just receive, assistance in the form of support, understanding, comfort, and suggestions about how to go on in life. In the long run, this empowers the bereaved and enhances their feelings of self-e cacy and ability to cope in bereavement (36,39). However, earlier research has shown that bereavement interventions provide therapeutic outcomes close to the post-intervention time but fail to last in follow-up (18).…”
Section: Discussionmentioning
confidence: 99%
“…Members in the groups bene t from opportunities to give, not just receive, assistance in the form of support, understanding, comfort, and suggestions about how to go on in life. In the long run, this empowers the bereaved and enhances their feelings of self-e cacy and ability to cope in bereavement (36,39). However, earlier research has shown that bereavement interventions provide therapeutic outcomes close to the post-intervention time but fail to last in follow-up (18).…”
Section: Discussionmentioning
confidence: 99%
“…Members in the groups benefit from opportunities to give, not just receive, assistance in the form of support, understanding, comfort, and suggestions about how to go on in life. In the long run, this empowers the bereaved and enhances their feelings of self-efficacy and ability to cope in bereavement [36,39]. However, earlier research has shown that bereavement interventions provide therapeutic outcomes close to the post-intervention time but fail to last in follow-up [18].…”
Section: Discussionmentioning
confidence: 99%
“…In the long run, this empowers the bereaved and enhances their feelings of self-efficacy and ability to cope in bereavement (36,39). However, earlier research has shown that bereavement interventions provide therapeutic outcomes close to the post-intervention time but fail to last in follow-up (18).…”
Section: Discussionmentioning
confidence: 99%